Growth performance and carcass characteristics of growing ram lambs fed sweet sorghum bagasse-based complete rations varying in roughage-to-concentrate ratios - Kumari, N.N.; Reddy, Y.R.; Blümmel, Michael; Nagalakshmi, D.; Monika, T.; Reddy, B.V.S.; Reddy, C.R. (Springer, 2013)
Different roughage-to-concentrate ratios of sweet sorghum bagasse (SSB) (a by-product of the biofuel industry)-based complete diets were assessed. Twenty four growing Nellore × Deccani ram lambs aged about 3 months (average body wt., 10.62±0.25 kg) were randomly allotted to four complete rations (CR) varying in roughage-toconcentrate ratios viz. 60:40 (CR-I), 50:50 (CR-II), 40:60 (CR-III) and 30:70(CR-IV) for a period of 180 days. The feed intake was comparable among the lambs fed different experimental complete diets. Average daily weight gain (in grams) was 77.31±4.90, 81.76±5.16, 85.83±2.83 and 86.30±3.25, and feed conversion ratio (in kilograms of feed per kilogram gain) averaged 11.42±0.68, 10.57±0.64, 10.17±0.37 and 9.96±0.38 in ram lambs fed CR-I, CR-II, CR-III and CR-IV rations, respectively. Statistically, differences in daily weight gain and feed conversion ratio among the lambs fed four experimental rations were not significant (P>0.05). The cost per kilogram gain was significantly (P< 0.01) higher in ram lambs fed CR-IV and CR-III rations compared to CR-I ration, and it was comparable between CR-I and CR-II rations. Dressing percentage averaged 44.90±0.15, 42.57±0.72, 43.67±0.16 and 44.42±0.76 for the respective diets. No significant difference and trend was observed in preslaughter weight, empty body weight, carcass weights, dressing percentage, wholesale cuts and edible and non-edible portions of experimental animals. Similarly, no significant variation could be seen in bone and meat yield (in per cent) and their ratios in various wholesale cuts among the dietary treatments. The roughage-to-concentrate ratio did not affect the chemical composition of meat; however, the fat content of meat was linearly increased with increase in the proportion of concentrate in the diets. The results of the experiment indicated that SSB can be included at 60 % level in the complete diet for economical mutton production from growing Nellore × Deccani ram lambs.